Vincenzo Tomeo’s legacy (Società e diritti, 2018)
Thirty years after the death of Vincenzo Tomeo, the Author proposes a scientific evaluation of the development of the thought of this Master of Sociology of Law  with some personal memories. His scientific work, which is almost entirely focused on an innovative and original view of social conflict, is above all a legacy of highest scientific and human value. Key words: Tomeo, Conflict, Judge, Hermeneutic